2015
DOI: 10.3390/magnetochemistry1010028
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and the Superatom Character of 13-Atom Platinum Nanoclusters

Abstract: 13-atom platinum nanoclusters have been synthesized quantitatively in the pores of the zeolites NaY and KL. They reveal highly interesting magnetic properties like high-spin states, a blocking temperature, and super-diamagnetism, depending heavily on the loading of chemisorbed hydrogen. Additionally, EPR active states are observed. All of these magnetic properties are understood best if one considers the near-spherical clusters as analogs of transition metal atoms with low-spin and high-spin states, and with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…For example, recent work on 13 atom Pt clusters shows a rich variety of magnetic effects that depend on the level of hydrogen loading. 36 Finally, Mu is widely known in quantum chemistry as a way to test first principles calculations and in particular quantum mass effects in H-atom reactivity. 37 The present study has established a route to extend Mu chemistry to metal surfaces.…”
mentioning
confidence: 99%
“…For example, recent work on 13 atom Pt clusters shows a rich variety of magnetic effects that depend on the level of hydrogen loading. 36 Finally, Mu is widely known in quantum chemistry as a way to test first principles calculations and in particular quantum mass effects in H-atom reactivity. 37 The present study has established a route to extend Mu chemistry to metal surfaces.…”
mentioning
confidence: 99%
“…It is already known that Pt has significant magnetic nature ( Paola et al, 2017 ; Albert and Rubin, 1964 ; Zhao et al, 2013 ; Du et al, 2014 ; Wang and Johnson, 2007 ). Also, experiments employing superconducting quantum interference device and x-ray magnetic circular dichroism have shown a magnetic behavior for Pt 13 when supported inside zeolite pores ( Roduner, 2014 ; Roduner and Jensen, 2015 ; Liu et al, 2006 ; Bartolomé et al, 2009 ), although these systems may differ from the perspective of the free nanoclusters in vacuum as discussed in the literature ( Paola et al, 2017 ). Nonetheless, it is also reported that other metal nanoclusters from the third transition series exhibit magnetic character at a low size regime ( Yamamoto et al, 2003 ; Roduner, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding structural, magnetic, and electronic characteristics of bimetallic Pt 13−n Ni n (n = 0–13) nanoclusters, some studies have shown that Ni does not provide any significant structural deformation but can weak the nanoalloy binding energy and increase its magnetic nature ( Jia et al, 2013 ; Zhao et al, 2013 ). Concerning the WGS reaction, theoretical studies of PtNi nanoclusters with different atomic quantities of Pt and Ni have been published, exposing the possibility of using those nanoclusters as catalysts ( de Souza Monteiro et al, 2008 ; Lin et al, 2011 ; Piotrowski et al, 2012 ; Zhao et al, 2013 ; Guedes-Sobrinho et al, 2015 ; Lian et al, 2015 ; Roduner and Jensen, 2015 ; Mokkath, 2018 ). Yet for the WGS reaction, previously computed adsorption energy values suggested that CO adsorption would occur more strongly than H 2 O on Pt 3 M (M = Cu, Mo, Ni, Rh) nanoclusters ( Lian et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Au, Ag, Cu, Pd or Pt). 7,8,9 Although some works have proposed alternative mechanisms, such as self-sustained persistent currents of conduction electrons, at this moment there is general consensus about the orbital nature of this magnetic moment, 1,10 The appearance of magnetization in capped GNPs was proposed to be associated with a spin symmetry breaking related with the 5d and 6s electrons of the Au atoms involved in the chemical bond with the ligands. The presence of the capping agents at the surface changes the number of uncompensated spins, which in turn modifies the relative spin densities at the Fermi energy, thus creating a non-zero magnetic moment.…”
Section: Introductionmentioning
confidence: 99%